The Jewish Neo-Aramaic dialect of Challa - Fassberg, Steven Ellis. (Studies in Semitic Languages and Linguistics, 2010)
Aramaic has been spoken uninterruptedly for more than 3000 years, yet a generation from now most Aramaic dialects will be extinct. The study of the Northeastern Neo-Aramaic (NENA) dialects has increased dramatically in the past decade as linguists seek to record these dialects before the disappearance of their last speakers. This work is a unique documentation of the now extinct Jewish Neo-Aramaic dialect of Challa (modern-day Çukurca, Turkey). It is based on recordings of the last native speaker of the dialect, who passed away in 2007. In addition to a grammatical description, it contains sample texts and a glossary of the dialect. Jewish Challa belongs to the cluster of NENA dialects known as 'lishana deni' and reference is made throughout to other dialects within this group.